Biomarker informed add-arm design for unimodal response. Issue 4 (3rd July 2016) - Wang, Jing; Chang, Mark; Menon, Sandeep
ABSTRACT: In this article, we propose a biomarker informed add-arm design for unimodal response. The new design contributes to optimizing the procedure of dose-finding when a biomarker of the study primary endpoint exists and prior evidence indicates a unimodal dose–response relationship. Designs with up to seven active treatment arms were considered. We propose the statistical approach for the Type I error control and carry out extensive simulation studies for the power performance of the design. The proposed design is shown to outperform the corresponding biomarker informed two-stage winner design in power on an average.